Accounting and Regulation New Insights on Governance, Markets and Institutions - Di Pietra, Roberto; McLeay, Stuart; Ronen, Joshua; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Since 1998, the world’s leading experts on accounting and regulation have convened in a series of workshops to explore emerging issues in their field, and to analyze the social and economic consequences. The workshops have covered a wide array of topics, including international standard setting, corporate governance, auditing, financial disclosure, and the dynamics of markets and institutions. They have addressed some of the most significant developments in the international financial economy, including the role that accounting practices and policies may have played in the global financial crisis.   In this volume, the editors select contributions to the workshops that are representative of the full spectrum of issues debated, illustrating the negotiable nature of the current regulatory framework of accounting. By challenging standard theories, and also providing a wealth of new evidence, this volume includes outstanding examples of state-of-the-art research, with a strong emphasis on the implications for accounting practice and policymaking.
Introduction -- Corporate Collapse: Regulatory, Accounting and Ethical Failure -- Post-Enron Reform: Financial Statement Insurance and GAAP Re-visited -- Accounting Standard Setting in Two Political Contexts -- Constituents’ Participation in the IASC/IASB’s Due Process of International Accounting Standard Setting: A Longitudinal Analysis -- A Crisis of Identity? A Juxtaposing Auditor Liability and the Value of Audit -- The Corporate Governance Effects of Audit Committee -- The Role of Debt Contracts and Debt Covenants in Corporate Governance: Reflections on Evolution and Innovation -- Regulation, Bonding and the Quality of Financial Statements -- Fair Value and the IASB/FASB Conceptual Framework Project: An Alternative View -- A Comparison of Historical Cost and Fair Value Accounting Systems: General and Some Regulatory Concerns -- IASB ED Management Commentary versus European Regulation: The Impact on Management’s Reports of Companies Listed on Italian Stock Exchange --  Do Attributes of Management’s Explanations of Financial Performance Matter for Analysts? An International Perspective -- The Consequences to Managers for Financial Misrepresentation -- National Standard-Setters’ Lobbying: An Analysis of its Role in the IFRS 2 Due Process -- Current State and Future Challenges of the IFRS: Some Thoughts -- Index.
Keywords: Accounting; Bookkeeping .; Finance; Accounting/Auditing.; Finance, general